The Financial Cost of Preventive and Curative Programs for Breast Cancer: A Case Study of Women in Shiraz-Iran - Nahid Hatam; Vahid Keshtkar; Asiyeh Salehi; Hamidreza Rafei (Kerman University of Medical Sciences, 2014)
Background This cross-sectional study was conducted to compare the average costs of breast cancer screening and treatment among women with the age of 25 and over in Shiraz-Iran. Methods Three majors hospitals affiliated with Shiraz University of Medical Sciences (SUMS) were selected for data collection. Financial documents and interviews with the hospitals' financial officers were used for data collection. Results Finding shows that the total cost of screening would be 5,847,544.96 US dollars for age groups of 25-34 and 35 and above, demonstrating the huge expense of screening programs. On the other hand, the average cost of breast cancer treatment for each patient would be 3608.47, 996.89, and 311.47 US dollars for mastectomy, radiotherapy, and chemotherapy, respectively. In addition, the total average cost for treatment of 2217 patients would be 1,466,988.9 US dollars, which is much less than screening programs expenses. Conclusion It is concluded that although screening can be effective for improving quality of life and treatment effectiveness, considering the high costs of screening, it is not economical in Iran. Screening methods within suitable intervals, and also considering patients' medical history have been recommended by the present study.